Corrections to “A Comprehensive Review of Direction-of-Arrival Estimation and Localization Approaches in Mixed-Field Sources Scenario” - Amir Masoud Molaei; Bijan Zakeri; Seyed Mehdi Hosseini Andargoli; Muhammad Ali Babar Abbasi; Vincent Fusco; Okan Yurduseven (IEEE Access)
Presents corrections to the paper, (Corrections to “A Comprehensive Review of Direction-of-Arrival Estimation and Localization Approaches in Mixed-Field Sources Scenario”).